Tinjauan Yuridis Resi Gudang Sebagai Instrumen Jaminan Berdasarkan Undang-Undang Nomor 9 Tahun 2011 Tentang Sistem Resi Gudang - Didiek Wahju Indarta; Lailatul Mutmainah (Dinasti Research, 2025)
A warehouse receipt is a document that proves the ownership and status of goods stored, regulated by Law Number 9 of 2011. Apart from being a means of proof, this receipt can also be used to obtain credit, supporting financial access for small and medium businesses. Law Number 9 of 2011 also regulates the responsibility of warehouse owners to maintain the security of goods and the validity of information in receipts, as well as demanding transparency and accountability. The debtor is obliged to maintain the condition of the goods pledged as collateral and fulfill debt payment obligations according to the agreement. The research method used is the Normative Juridical method. The results of research on the mechanism for using warehouse receipts as collateral in financing and credit show that legally, warehouse receipts function as legal financing instruments in accordance with Law Number 9 of 2011. Their use in financing refers to procedures involving the transfer of ownership rights to goods stored to creditors as collateral. The responsibility of the warehouse owner is to maintain the security and validity of the goods information contained in the receipt and to act transparently and accountably so that the warehouse receipt can be trusted by creditors. Meanwhile, debtors who use warehouse receipts as credit instruments have an obligation to maintain the condition of the goods guaranteed and fulfill debt payments according to the applicable agreement, so that the relationship between all parties in the financing process runs well.